2007
DOI: 10.1086/510348
|View full text |Cite
|
Sign up to set email alerts
|

Trigonometric Parallaxes of Central Stars of Planetary Nebulae

Abstract: Trigonometric parallaxes of 16 nearby planetary nebulae are presented, including reduced errors for seven objects with previous initial results and results for six new objects. The median error in the parallax is 0.42 mas, and twelve nebulae have parallax errors less than 20 percent. The parallax for PHL932 is found here to be smaller than was measured by Hipparcos, and this peculiar object is discussed. Comparisons are made with other distance estimates. The distances determined from these parallaxes tend to … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
111
3

Year Published

2008
2008
2013
2013

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(127 citation statements)
references
References 31 publications
13
111
3
Order By: Relevance
“…In addition, the spectral energy distribution derived from available optical and 2MASS data (Arp & Scargle 1967;Wesemael et al 1992;Allard et al 1994;Cutri et al 2003;Harris et al 2007) is consistent with no near-IR excess from a cool companion.…”
Section: Non-binary Status Of Phl 932mentioning
confidence: 54%
See 1 more Smart Citation
“…In addition, the spectral energy distribution derived from available optical and 2MASS data (Arp & Scargle 1967;Wesemael et al 1992;Allard et al 1994;Cutri et al 2003;Harris et al 2007) is consistent with no near-IR excess from a cool companion.…”
Section: Non-binary Status Of Phl 932mentioning
confidence: 54%
“…The revised Hipparcos catalog gives a distance of 113(+114, −38) pc (van Leeuwen 2007), however this value, as with the original Hipparcos parallax leads to an non-physical stellar mass for PHL 932 of <0.1 M . An improved parallax of 3.36 ± 0.62 mas (Harris et al 2007) has shown that the Hipparcos value is in error. We adopt the new parallax distance of 298(+67, −47) pc hereafter.…”
Section: Spectral Analysis and Distancementioning
confidence: 98%
“…The added incentive here is that the absolute magnitudes obtained from parallaxes are completely model independent. We have 92 DA white dwarfs in our sample with available parallax measurements from either the Yale Parallax Catalogue (van Altena et al 1995), or Hipparcos (Perryman & ESA 1997) and 9 central stars of planetary nebulae with parallaxes taken from Harris et al (2007). We present in Figure 29 the comparison between the M V values from parallax measurements and those obtained through our spectroscopic analysis.…”
Section: Comparison With Parallax Measurementsmentioning
confidence: 99%
“…For the remaining 3 PNe, NGC 6826, NGC 2392 and IC 418 our individual distances are about 45% smaller than those given by Mendez et al (1992). For the single PN for which an optical parallax is available, NGC 7293, Harris et al (2007) measure a distance of 219 pc while Mendez et al (1992) give the higher value of 300 pc. We regard the values of Mendez et al as rather high and do not give tham much weight.…”
Section: Referencesmentioning
confidence: 99%